A review on segmentation of knee articular cartilage: from conventional methods towards deep learning - Ebrahimkhani, Somayeh; Jaward, Mohamed Hisham; Cicuttini, Flavia M.; Dharmaratne, Anuja; Wang, Yuanyuan; de Herrera, Alba G. Seco (Artificial intelligence in medicine, 2020)
•We present a review of knee articular cartilage segmentation methods.•The use of convolutional neural networks (CNNs) has grown in knee articular cartilage segmentation. Therefore, these methods are presented in a separate section.•Quantitative results are represented, pointing out pros and cons of reviewed studies.•This review presents an updated and comprehensive review in the field. In this paper, we review the state-of-the-art approaches for knee articular cartilage segmentation from conventional techniques to deep learning (DL) based techniques. Knee articular cartilage segmentation on magnetic resonance (MR) images is of great importance in early diagnosis of osteoarthritis (OA). Besides, segmentation allows estimating the articular cartilage loss rate which is utilised in clinical practice for assessing the disease progression and morphological changes. It has been traditionally applied in quantifying longitudinal knee OA progression pattern to detect and assess the articular cartilage thickness and volume. Topics covered include various image processing algorithms and major features of different segmentation techniques, feature computations and the performance evaluation metrics. This paper is intended to provide researchers with a broad overview of the currently existing methods in the field, as well as to highlight the shortcomings and potential considerations in the application at clinical practice. The survey showed that state-of-the-art techniques based on DL outperform the other segmentation methods. The analysis of the existing methods reveals that integration of DL-based algorithms with other traditional model-based approaches has achieved the best results (mean Dice similarity coefficient (DSC) between 85.8% and 90%).